(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Menstrual disorders are a common presentation by late adolescence; 75% of girls experience some problems associated with menstruation including delayed, irregular, painful, and heavy menstrual bleeding, which are the leading reasons for the physician office visits by adolescents. The journey from puberty to maturity is known as adolescence. Menarche is one of the puberty markers, and as such, it is an essential occurrence in the lives of adolescent girls. a prevalence study was conducted among college going females at Coimbatore city with objective to study prevalence of primary menstruation in young females and to examine problems associated with menstruation in selected respondents . The cross-sectional study was conducted by the researcher for the current study, for a period of 3 months (June 2020 to August 2020). The study was performed on a total of 1106 girls and 685 agreed to voluntarily participate in the study. The study it can be identified that most of the respondents are facing issues like backache, headache, anxiety, tension during their cycle. And many are facing irregular menstrual cycle. a broad understanding of the sexual and reproductive health issues the adolescents and youth face today is menstrual cycle.